1981
DOI: 10.1088/0034-4885/44/9/001
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting microbridges exhibiting Josephson properties

Abstract: In films of superconducting tin, indium and aluminium it is possible to make constrictions on a scale smaller than the coherence length over a fairly large temperature range. The ground-state Cooper pairs in and around such a microbridge give rise to properties similar to those observed in classic Josephson tunnel junctions. However, in the microbridge the normal electrons thermally excited out of the superconducting ground state may be associated with very large current densities governed by a non-equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 88 publications
3
29
0
Order By: Relevance
“…3͑a͔͒, thus representing the non-Josephson oscillation. 8 The Josephson frequencies f J on the three arrow-marked bias points in Fig. 3͑a͒ are equal to 142.82 GHz, 143.30 GHz, and 143.58 GHz, while the observed radiation frequencies are 142.94 GHz, 143.18 GHz, and 143.25 GHz, respectively.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…3͑a͔͒, thus representing the non-Josephson oscillation. 8 The Josephson frequencies f J on the three arrow-marked bias points in Fig. 3͑a͒ are equal to 142.82 GHz, 143.30 GHz, and 143.58 GHz, while the observed radiation frequencies are 142.94 GHz, 143.18 GHz, and 143.25 GHz, respectively.…”
mentioning
confidence: 93%
“…6,7 When Josephson junctions are strongly coupled to a resonator, self-induced steps, and non-Josephson oscillation can be observed. 8 The non-Josephson radiation was first detected in 1966 from a single point-contact Josephson junction coupled to a rectangular cavity. 9 Further theoretical investigations were performed by Auracher and Van Duzer 10 and experiments by Kanter. 11 The parametric negativeresistance effect generated by the quantum-phase-dependent inductance of the Josephson junction L J , was considered to be the explanation of the self-induced steps and of the nonJosephson oscillation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Especially they found that at T =F 0 the static conductivity is of activation type, the activation energy of which decreases linearly in proportion to the electric field. In this non-Ohmic conduction process, and also for the Ohmic conduction at T =F 0, the large local changes of 0 overcoming the potential barriers are essential (see also [144]). …”
Section: Jnl E Iamentioning
confidence: 99%